HYDROLOGICAL MODELLING FOR EVALUATING CLIMATE CHANGE IMPACTS ON STREAMFLOW REGIME IN THE BERNAM RIVER BASIN MALAYSIA (FUDMA JOURNAL OF SCIENCES, 2021)
The complexity of hydrological models has been a setback in their evaluation particularly for long-term simulations. Deficit and constant loss (DCL) method has been introduced in Hydrologic Engineering Center's Hydraulic Modeling System (HEC-HMS) model for continuous based simulations. However, studies on climate change impacts using the method are still very few. This study used the method to evaluate potential impacts of climate change on streamflow at Bernam Basin, Malaysia for 2010-2039, 2040-2069 and 2070-2099 to the baseline period (1976-2005) under two RCP scenarios (RCPs 4.5 and 8.5). The model efficiency during evaluation is found satisfactory. Compared with the baseline period, the predicted streamflow   decreased in all future periods during main and off-seasons. However, the changes have become more pronounced during the off-season with a significant decrease of 9.14% under the worst-case scenario (RCP8.5). Therefore, the Basin would likely experience tremendous pressure in the late century due to low streamflow, particularly in off-season months.
Keywords: Climate change; deficit and constant loss method; flow regime; HEC-HMS; hydrological model